EFFECT OF FLUOXETINE ON SLEEP ARCHITECTURE IN PATIENTS WITH METABOLIC SYNDROME AND OBSTRUCTIVE SLEEP APNEA SYNDROME - O. V. Lyubshina; A. L. Vertkin; M. Yu. Maksimova (Рациональная фармакотерапия в кардиологии)
Aim. To study effect of fluoxetine on sleep architecture in patients with metabolic syndrome and obstructive sleep apnea syndrome.Material and methods. 98 patients with obstructive sleep apnea syndrome and metabolic syndrome (aged 54.3±8.7 y.o.) were included into the study. All patients received fluoxetine 20 mg once daily during 6 months. Influence of fluoxetine on sleep architecture was evaluated with special questionnaire and by polysomnography, including electroencephalogram, electrooculogram, mentalis electromyogram and pulseoxymetry.Results. Decrease in wake time after sleep onset (Δ33%; р<0.05) was found at the end of treatment. It resulted in improvement of sleep efficacy index. Decrease in respiratory sleep disorders index (Δ20%) and rising of blood oxygen saturation (Δ12%; р<0.05) was also found. Improvement of the sleep architecture (reduction in the 2nd phase of slow wave sleep by 15%, increase in delta-sleep (Δ71%) and rapid eye movement sleep (Δ25%; р<0.05) was also observed. Besides reduction in body mass index after fluoxetine therapy (Δ12%; р<0.05) was found. Serious adverse effects were not registered.Conclusion. Fluoxetine use in patients with metabolic syndrome and obstructive sleep apnea syndrome shown positive effect on objective indices of sleep architecture and respiratory sleep disorders. It improved adaptive function of the sleep and contributed to reduction in sleep disorders.